Disparities in the PrEP continuum for trans women compared to MSM in San Francisco, California: results from population‐based cross‐sectional behavioural surveillance studies. (30th June 2020) - Wilson, Erin C; Turner, Caitlin M; Arayasirikul, Sean; Lightfoot, Marguerita; Scheer, Susan; Raymond, Henry F; Liu, Albert
Abstract: Introduction: Although transgender women (trans women) often are conflated with men who have sex with men (MSM) in HIV research and services, there are distinct population differences that are important for implementing effective HIV prevention. Our objective was to examine pre‐exposure prophylaxis (PrEP) disparities between the two populations and compare individual, social and structural factors that influence differences between MSM and trans women along the PrEP continuum. Methods: We analysed data from two population‐based studies, one with trans women (Trans*National Study, 2016 ‐ 18) and the other with MSM (National HIV Behavioral Surveillance, 2017). Trans women were recruited via respondent‐driven sampling and MSM using time location sampling. Key indicators of the PrEP continuum were evaluated, including awareness, health insurance, provider discussions, recent use and adherence. Associations were also examined for PrEP continuum indicators and structural barriers (e.g. employment, homelessness). Results: Transwomen were more likely than MSM to be Latino/a (30.4% vs. 25.8%; prevalence ratio (PR)=1.08, 95% CI 1.02 to 1.14) or African American (7.1% vs. 4.5%; PR = 1.12, 1.02 to 1.24), live at or below the poverty limit (70.7% vs. 15.8%; PR = 1.47; 1.41 to 1.53), be unemployed (50.1% vs. 26.3%; PR = 1.18, 1.13 to 1.24), be homeless (8.4% vs. 3.5%; PR = 1.15, 1.06 to 1.25) and to have less than a college degree (PR = 1.41, 1.34 to 1.48). Trans women were more likely than MSM to have health insurance (95.7% vs. 89.7%, PR = 1.17, 1.06 to 1.28), but less likely than MSM to have heard of PrEP (79.1% vs. 96.7%; PR = 0.77, 0.73 to 0.81), talked with a provider about PrEP (35.5% vs. 54.9%; PR = 0.87, 0.83 to 0.91) and less likely than MSM to have used PrEP in the past six months (14.6% vs. 39.8%; PR = 0.80, 0.76 to 0.84). Among PrEP users, trans women were less likely to report being adherent to PrEP than MSM (70.4% vs. 87.4%; PR = 0.80, 0.70 to 0.91). Conclusions: We found PrEP disparities for trans women compared to MSM and the need for differentiated implementation strategies to meet the specific PrEP barriers trans women face. Inclusion of trans women's HIV risks is needed in CDC guidance for PrEP. Interventions to increase trans women's awareness of PrEP including at the provider and community level are also needed. Finally, programming that addresses trans women's barriers to housing and income is also needed to reduce PrEP disparities.